Home automated system using Bluetooth and an android application - Abiodun E. Amoran; Ayodele S. Oluwole; Enitan O. Fagorola; R.S. Diarah (Scientific African, 2021)
This article describes the implementation of a Bluetooth technology and an android application with voice prompts based home-automated system using an Arduino microcontroller. The system is aimed at designing an automated appliance control that is user-friendly and convenient to use. The design comprised an Arduino ATMEGA328 microcontroller board, Bluetooth module (HC-06), and an android application (MIT App Inventor 2). The Arduino controls any connected component and was programmed with C++ programming language by using Integrated Development Environment (IDE). Relays and Triacs are used for the switching mechanism. Once the system is connected, the user controls the electrical appliances connected to the home-automated system, which can also be controlled using voice prompt with the help of a Google assistant inbuilt with the android smartphone. The system switches the home appliances ON and OFF using the android app, Bluetooth module, and voiced prompt. It can also be timed to switch off appliances for a pre-time of 12 h, thus making the application easy and convenient to operate via a smartphone.